PENGARUH EDUKASI TATALAKSANA TIDUR DAN PIJAT KAKI (FOOT MASSAGE) TERHADAP KUALITAS TIDUR PADA PENDERITA DIABETES MELITUS TIPE 2 DI WILAYAH KERJA PUSKESMAS KOTA BENGKULU - Hendri Heriyanto; Fauzan Efendi; Erni Buston (Poltekkes Kemenkes Bengkulu, 2021)
Background : Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia or high levels of glucose in the blood due to impaired insulin secretion, decreased insulin action or a result of both. The risk of developing type 2 diabetes will continue to increase with increasing age, obesity, and lack of physical activity (American Diabetes Association, 2018). Objective: To determine the effect of providing sleep management books and foot massage on sleep quality values ​​in patients with type II diabetes mellitus. Research Methods: The design used in this study was One group pre test - post test design, where in this study the sample was observed first before being given treatment then after being given treatment the sample was re-observed (Hidayat, 2007). Results: The results of statistical tests with the Wilcoxon Sign Rank Test at α 5% obtained a sleep quality score (p value 0.035 <0.05) So Ha is accepted. Conclusion: there is an effect of sleep management books and foot massage on changes in sleep quality scores and Ankle Brachial Index values.